Indicator pollen taxa of human-induced and natural vegetation in Northern China. (April 2015) - Li, Manyue; Xu, Qinghai; Zhang, Shengrui; Li, Yuecong; Ding, Wei; Li, Jianyong
Research on modern pollen assemblages of human-induced vegetation is conducive to extracting human impact information, and provides basis for determining human impact intensity. The use of 189 surface soil pollen samples from human-induced and natural vegetation shows that there were significant discrepancies of indicator pollen taxa and human impact intensity between different vegetation types in Northern China. The results demonstrate that forest and grassland pollen assemblages are dominated by natural vegetation pollen taxa, which show little effect from human impact. Farmlands are dominated by Cereal Poaceae pollen. Cultivation methods, climate conditions and human impact intensity are the main reasons that cause discrepancy in different regions. Uncultivated lands could be effectively distinguished based on common human-companion plant pollen types and certain amount of crop pollen, which display the first step of secondary succession from human-induced to natural vegetation. Indicator species analysis shows that Cereal Poaceae, Trilete spore, Humulus and Brassicaceae indicate farmlands; weeds Poaceae, Chenopodiaceae, Ranunculaceae and Selaginella sinensis indicate uncultivated lands; grasslands have the largest number of indicator pollen taxa, in which Convolvulaceae, Artemisia, Asteraceae, Liliaceae, Polygonaceae, and Nitraria pollen have the highest indicator values; in forests, Betula, Larix and Quercus have the highest indicator values with statistical significance. Meanwhile, Human Influence Index (HII) values can be used to differentiate human-induced and natural vegetation. The calibration model of pollen-HII based on the weighted averaging plus partial least squares (WA-PLS) method exhibits a good statistical performance ( R 2 = 0.69), and the HII values have the same trend of change with Cereal Poaceae percentage. Our results confirm that pollen from human-induced vegetation can provide reliable estimates of HII, which provides a good reference for restoring human impact intensity in fossil pollen assemblage.